2020
DOI: 10.5713/ajas.18.0767
|View full text |Cite
|
Sign up to set email alerts
|

A whole genome sequence association study of muscle fiber traits in a White Duroc×Erhualian F2 resource population

Abstract: Objective: Muscle fiber types, numbers and area are crucial aspects associated with meat production and quality. However, there are few studies of pig muscle fibre traits in terms of the detection power, false discovery rate and confidence interval precision of whole-genome quantitative trait loci (QTL). We had previously performed genome scanning for muscle fibre traits using 183 microsatellites and detected 8 significant QTLs in a White Duroc× Erhualian F2 population. The confidence intervals of these QTLs r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…GATM and SEMA5A are involved in placental development and embryonic development, respectively [ 51 , 52 ]. HDAC9 and GRM8 are associated with eye muscle area and the relative area of type I fibers, respectively [ 53 , 54 ]. ITGAL is immune-related and involved in leukocyte recruitment processes [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…GATM and SEMA5A are involved in placental development and embryonic development, respectively [ 51 , 52 ]. HDAC9 and GRM8 are associated with eye muscle area and the relative area of type I fibers, respectively [ 53 , 54 ]. ITGAL is immune-related and involved in leukocyte recruitment processes [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, most of the SNPs and candidate genes for important economic traits of pigs identified based on GWAS mainly used F2 generation populations, which were generated by crossbreeding local pig breeds from different countries with Western lean pig breeds ( Liu et al, 2014 ; Zhang et al, 2014 ; Cho et al, 2015 ; Guo et al, 2020 ; Liu et al, 2020 ) and purebred pigs ( Xiong et al, 2015 ; Ding et al, 2019 ; Fabbri et al, 2020 ; Fu et al, 2020 ). The F2 generation population is characterized by segregation of traits, large phenotypic variation and more genetic diversity, which is suitable for GWAS.…”
Section: Discussionmentioning
confidence: 99%
“…The F2 generation population is characterized by segregation of traits, large phenotypic variation and more genetic diversity, which is suitable for GWAS. Some studies use white Duroc × Erhualian F2 hybrid pig population to conduct GWAS on growth, fat, meat quality, muscle fiber, body size and body weight traits ( Ma et al, 2013 ; Qiao et al, 2015 ; Guo et al, 2017 ; Ji et al, 2017 ; Guo et al, 2020 ), and obtained a large number of mutation sites and candidate genes related to the research traits. Besides, two studies used Large White × Minzhu F2 generation population to perform GWAS on meat quality and external traits ( Luo et al, 2012 ; Wang et al, 2014 ), and identified some SNP loci and candidate genes related to meat quality and external traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation